PADRÃO DE VARIAÇÃO FACIAL COMO MEDIADOR DE INTERAÇÕES EM COLÔNIAS DE VESPAS SOCIAIS - BATISTA, Nathan Rodrigues; SGUARIZI-ANTONIO, Denise; NEVES, Erika Fernandes; ANTONIALLI-JUNIOR, William Fernando (ANAIS DO ENIC, 2017)
-